2006
DOI: 10.1007/s11270-006-9276-x
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution Processing by Radiation Fogs

Abstract: Several fog episodes occurred in California's San Joaquin Valley during winter 2000/2001.Measurements revealed the fogs to generally be less than 50 m deep, but to contain high liquid water contents (frequently exceeding 200 mg/m 3 ) and large droplets. The composition of the fog water was dominated by ammonium (median concentration= 608 μN), nitrate (304 μN), and organic carbon (6.9 ppmC), with significant contributions also from nitrite (18 μN) and sulfate (56 μN). Principal organic species included formate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
69
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 44 publications
3
69
0
Order By: Relevance
“…Several studies have reported sulphate production by fog/clouds (Laj et al, 1997). However, recent measurements of fog sample composition (Herckes et al, 2007a) show domination by nitrogen species, with ammonium and nitrate being the most abundant compounds. Fog droplets were found to have a pH well above 6, showing a significant decrease in fog concentration of sulphate and increase in fog pH in comparison to samples taken before the 1980s.…”
Section: Aerosol Characterizationmentioning
confidence: 99%
“…Several studies have reported sulphate production by fog/clouds (Laj et al, 1997). However, recent measurements of fog sample composition (Herckes et al, 2007a) show domination by nitrogen species, with ammonium and nitrate being the most abundant compounds. Fog droplets were found to have a pH well above 6, showing a significant decrease in fog concentration of sulphate and increase in fog pH in comparison to samples taken before the 1980s.…”
Section: Aerosol Characterizationmentioning
confidence: 99%
“…The chemical composition of two is a cumulative outcome of gas-liquid-solid heterogeneous interactions. However, fog chemistry is influenced by number and composition of the particles, gaseous species (Herckes et al, 2007;Lekouch et al, 2011) as well as by the moisture content and temperature in ambient atmosphere. Dew water chemistry is also influenced by nature of surface on which it is formed (Beysens et al, 2006;Lekouch et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Fog chemistry has been widely studied at California and other locations of USA by Collett et al (2008Collett et al ( , 2002Collett et al ( , 1999; Herckes et al (2007). They have studied chemical composition, organic acids and buffering capacities of fog water.…”
Section: Introductionmentioning
confidence: 99%
“…1995; Elias et al 1995;Mindas & Skvarenina 1995;Skvareninova & Skvarenina 2000;Elbert et al 2000;Acker et al 2002;Migala et al 2002;Herckes et al 2007;Zapletal et al 2007;Mihalikova et al 2008). We have been concerned with these problems in our previous work for example , Fisak et al (2002, Fisak et al ( , 2006a.…”
Section: Introductionmentioning
confidence: 99%